Assessment of vertical radiocesium transfer in soil via roots. (October 2020) - Sakashita, Wataru; Miura, Satoru; Akama, Akio; Ohashi, Shinta; Ikeda, Shigeto; Saitoh, Tomoyuki; Komatsu, Masabumi; Shinomiya, Yoshiki; Kaneko, Shinji
Abstract: Several years after the Fukushima Daiichi Nuclear Power Plant accident, the surface mineral soil layer is believed to be the main reservoir of radiocesium ( 137 Cs) in forest ecosystems in Japan. Dissolved 137 Cs combines with clay minerals in the soil, and hence, it is not expected to easily infiltrate over time. However, previous studies have indicated that 137 Cs derived from the older global fallout migrated deeper than that of the Chernobyl accident, and this cannot be explained by only the dissolved 137 Cs vertical migration in the soil. Considering the carbon and nutrient dynamics in the forest floor, the 137 Cs transfer process in soil via roots may alter its vertical distribution on a decadal scale. Therefore, in this study, we investigated the 137 Cs activity concentrations in both roots and soil matrix, by considering four (0–20 cm) or six (0–30 cm) mineral soil layers taken at every 5 cm at seven study sites dominated by one of the six plant species (three coniferous forests, one deciduous forest, two deciduous forests covered by Sasa, and one bamboo forest) in eastern Japan in 2013. Comparing the results of 137 Cs activity concentrations between roots and soil matrix taken at the same soil layer, roots at the surface (0–5 cm) layer often showed lower values than the soil matrix. However, roots deeper than 5 cm had higher activity concentrations than the soil matrix, conversely. The 137 Cs inventories ratio of roots to soil matrix are about 1% at the 0–5 and 5–10 cm soil layer, and about 2% at the soil layers deeper than 10 cm. These results suggest that decomposition of root litter little affect the short-term vertical migration of 137 Cs in the forest soil. However, it indicates that continuous production and mortality of roots with relatively high 137 Cs activity concentrations have an important role for changing the vertical distribution of 137 Cs on time scale of decades, particularly at deeper soil layers. Highlights: We evaluated whether root turnover contribute for changing the vertical distribution of 137 Cs in soil matrix. 137 Cs inventory ratio of roots to soil matrix are 1% at shallow soil layer (0–10 cm) and 2% at the layer deeper than 10 cm. Continuous root turnover can change the vertical distribution of 137 Cs in soil on time scale of decades.